2017
DOI: 10.1159/000484979
|View full text |Cite
|
Sign up to set email alerts
|

Alicaforsen, an Antisense Inhibitor of Intercellular Adhesion Molecule-1, in the Treatment for Left-Sided Ulcerative Colitis and Ulcerative Proctitis

Abstract: Background: Data on the efficacy of intercellular adhesion molecule-1 antisense oligonucleotide alicaforsen in ulcerative colitis (UC) is inconsistent. Methods: All patients, who had received at least one dose of alicaforsen, were analyzed retrospectively. Alicaforsen’s efficacy was assessed in patients treated for left-sided UC and proctitis by comparing clinical and (if applicable) endoscopic disease activity before/after treatment. Results: Twelve patients were treated for left-sided UC or proctitis. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The toxicity of PS-AONs in vivo has been an important issue, however. Alicaforsen (ISIS 2302), a 20-nt PS ODN complementary to a part of the human intercellular adhesion molecule-1 mRNA (18), has been studied extensively as an enema-applied treatment for ulcerative colitis (19), inflammatory bowel disease (20), and pouchitis (21). Identified problems included immune stimulation (mice, 20 mg/kg) (22), increases in aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in serum suggestive of hepatic damage (mice, 100 mg/kg) (23), lethargy, changes in blood clotting time and atrophic processes in kidneys (monkeys, 10 mg/kg) (24), and red blood cells in the renal lumen (monkeys, 50 mg/kg) (25, 26).…”
mentioning
confidence: 99%
“…The toxicity of PS-AONs in vivo has been an important issue, however. Alicaforsen (ISIS 2302), a 20-nt PS ODN complementary to a part of the human intercellular adhesion molecule-1 mRNA (18), has been studied extensively as an enema-applied treatment for ulcerative colitis (19), inflammatory bowel disease (20), and pouchitis (21). Identified problems included immune stimulation (mice, 20 mg/kg) (22), increases in aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels in serum suggestive of hepatic damage (mice, 100 mg/kg) (23), lethargy, changes in blood clotting time and atrophic processes in kidneys (monkeys, 10 mg/kg) (24), and red blood cells in the renal lumen (monkeys, 50 mg/kg) (25, 26).…”
mentioning
confidence: 99%
“…This a4 integrin antagonist could also induce clinical remission in patients with UC but not with CD [151,152]. Furthermore, alicaforsen, a synthetic antisense oligonucleotide against the adhesion molecule ICAM-1, proved to be effective in patients with UC in phase 2 trials and especially in patients with UC-related pouchitis in phase 3 trials [153][154][155][156][157][158][159][160], whereas in patients with CD, alicaforsen did not significantly improve the clinical outcome [161][162][163][164][165]. Additionally, it was observed that a telluriumbased compound could preserve the colonic epithelium integrity in the DSS colitis mouse model by preventing the migration of a4β7 + macrophages to the colon and the adhesion of MLN cells to MadCAM-1 both in vitro and in vivo.…”
Section: Adhesion Molecule Targeting As a Treatment Optionmentioning
confidence: 99%
“…The most frequent adverse events were asthenia, infections, and nausea. No serious adverse events related to the medical treatment[ 124 ]. In another phase 2 clinical trial, no significant difference was observed between treatment arms and placebo in the primary endpoint[ 125 ].…”
Section: Focused Therapy On the Integrity Of The Epithelial Barriermentioning
confidence: 99%